Growth Performance of Gracilaria sp. in Relation to Nitrogen Uptake from Effluents of Shrimp Culture at Varying Stocking Densities: Growth Performance of Gracilaria sp. in Relation to Nitrogen Uptake from Effluents of Shrimp Culture at Varying Stocking Densities - Restiana Wisnu Ariyati; Lestari Lakhsmi Widowati; Ichwanus Sofa Alkisai; sri Rejeki; Sarjito; Alfabetian Herjuno Condro Haditomo; Dicky Harwanto; Roel H. Bosma (Journal of Aquaculture and Fish Health, 2026)
The growth performance of Gracilaria sp. is influenced by its ability to absorb excess nutrients, particularly nitrogen, from aquaculture effluents. This study aimed to evaluate the nitrogen uptake and growth rate of Gracilaria verucosa cultivated in a mesocosm system receiving effluents from black tiger shrimp (Penaeus monodon) cultured at different stocking densities. Post larvae (PL-20) with an initial body weight of 0.4 ± 0.1 g were reared for 28 days at three shrimp stocking densities (20, 60, and 100 PL m⁻²) integrated in a recirculation system with Gracilaria. The highest nitrogen uptake rate by Gracilaria (11.36 mg DW m⁻² day⁻¹) was recorded under the highest shrimp density (100 PL m⁻²). A significant correlation (R² = 0.7) was identified between nitrogen absorption and the growth rate of Gracilaria sp., with the highest growth rate (2.24 ± 0.08% day⁻¹) recorded at this density. However, nitrogen retention in Gracilaria was not significantly affected by the different effluent concentrations. These findings suggest that higher shrimp densities can enhance nitrogen uptake and stimulate Gracilaria growth in integrated aquaculture systems.